Mergers in the Digital Economy - Axel Gautier; Joe Lamesch (Center for Economic Studies and ifo Institute (CESifo), 2020)
Over the period 2015-2017, the five giant technologically leading firms, Google, Amazon, Facebook, Amazon and Microsoft (GAFAM) acquired 175 companies, from small start-ups to billion dollar deals. By investigating this intense M&A, this paper ambitions a better understanding of the Big Five's strategies. To do so, we identify 6 different user groups gravitating around these multi-sided companies along with each company's most important market segments. We then track their mergers and acquisitions and match them with the segments. This exercise shows that these five firms use M&A activity mostly to strengthen their core market segments but rarely to expand their activities into new ones. Furthermore, most of the acquired products are shut down post acquisition, which suggests that GAFAM mainly acquire firm's assets (functionality, technology, talent or IP) to integrate them in their ecosystem rather than the products and users themselves. For these tech giants, therefore, acquisition appears to be a substitute for in-house R&D. Finally, from our check for possible "killer acquisitions", it appears that just a single one in our sample could potentially be qualified as such.
Keywords: D43; K21; L40; L86; G34; 330; mergers; GAFAM; platform; digital markets; competition policy; killer acquisition